2009
DOI: 10.1111/j.1399-5448.2009.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up results on monitoring and discussing health-related quality of life in adolescent diabetes care: benefits do not sustain in routine practice

Abstract: The beneficial effects of an office-based HRQoL intervention in adolescents with diabetes largely disappear 1 year after withdrawing the HRQoL assessment procedure. This finding underscores the importance of integrating standardized evaluation and discussion of HRQoL in routine care for adolescents with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Mean goal-related self-efficacy was 3.08 (SD = .34). Mean positive mood was 16.65 (M CF = 17.62; M dia = 15.35), whereas mean negative mood was 3.72 (M CF = 2.87; M dia = 4.85), which seems to be in line with previous research in adolescents with CF and diabetes (e.g., Casier et al, 2011;De Wit et al, 2010). The mean for goal facilitation was 9.53 (SD = 7.05) and 2.71 (SD = 4.01) for goal interference.…”
Section: Aggregated Datasupporting
confidence: 91%
“…Mean goal-related self-efficacy was 3.08 (SD = .34). Mean positive mood was 16.65 (M CF = 17.62; M dia = 15.35), whereas mean negative mood was 3.72 (M CF = 2.87; M dia = 4.85), which seems to be in line with previous research in adolescents with CF and diabetes (e.g., Casier et al, 2011;De Wit et al, 2010). The mean for goal facilitation was 9.53 (SD = 7.05) and 2.71 (SD = 4.01) for goal interference.…”
Section: Aggregated Datasupporting
confidence: 91%
“…Continuous support delivered by a diabetes MDT may be equally as important as short-term interventions. DeWit et al 94,95 reported that asking young people about QoL during clinic visits improved QoL and satisfaction with care but had no effect on glycaemic control.…”
Section: Focusing On Psychological Therapiesmentioning
confidence: 99%
“…The greatest outcome benefits may be beyond measures of glycaemic control, and therefore, it is important to measure children's perceived health-related quality of life (HrQoL) (Müller-Godeffroy et al, 2009) and to consider such variables in national quality registries. To enable optimal care for children with diabetes, it is important to include attention not just to medical outcomes but to HrQoL as well and a contingence to detect psychological problems that otherwise could be missed (de Wit et al, 2010). Early identification of children at risk of developing poor HrQoL may increase treatment compliance (Cameron, 2003).…”
Section: Introductionmentioning
confidence: 99%